Analyzing the effect of steam quality and injection temperature on the performance of steam flooding - Kirmani, Farzain Ud Din; Raza, Arshad; Gholami, Raoof; Haidar, Muhammad Zeshan; Fareed, Chaudary Sarosh (Energy Geoscience, 2021)
The heavy oil reservoirs are currently mainly targeted by thermal enhanced oil recovery technologies, particularly, steam flooding. Steam flooding is carried out by introducing heat into the reservoir to unlock the recovery of heavy oil by reducing oil viscosity. Several investigations were carried out to improve oil recovery by steam flooding. Most recently, high steam flooding is reported as an effective approach to improve recovery in high pressure heavy oil reservoirs. The oil recovery from steam flooding is substantially affected by the steam quality and injection temperature. In this study, an attempt was made to look into the integration of parameters, i.e. steam quality and injection temperature upon steam flooding on oil recovery by using a simulation approach via ECLIPSE. The results obtained indicated that high temperature along with the moderate value of steam quality gives the best result regarding oil recovery for steam flooding in an economical way. [Display omitted] •Steam flooding is affected by steam quality and injection temperature.•Temperature is directly related to recovery with high-quality steam.•Steam is directly related to recovery at low and moderate temperature.